CHALLENGES IN TREATMENT OF RENAL GRAFT ACUTE ANTIBODY-MEDIATED REJECTION - A. I. Sushkov; A. V. Sharshatkin (Вестник трансплантологии и искусственных органов, 2016)
Diagnostic criteria and treatment protocols for acute antibody-mediated rejection (AMR) of kidney allograft remain controversial. We report the case of early severe AMR after primary kidney transplantation. The graft removal was considered in the absence of treatment efficacy and in the presence of systemic infl ammatory response syndrome. However, at surgery the graft looked normal and it was not removed. The repeated treatment course (plasmapheresis, antithymocyte globulin, intravenous immunoglobulin and rituximab) was effective. The patient has good and stable graft function in 1 year after transplantation.